Soundness and compressive strength of Portland cement blended with ground granulated ferronickel slag - Rahman, Md Ashiqur; Sarker, Prabir; Shaikh, Faiz; Saha, Ashish (Elsevier BV, 2017)
This paper evaluates the fresh and hardened properties of cement pastes and mortars blended with a ground granulated high-magnesium ferronickel slag (FNS). The main elements of the slag are Silicon (Si), Magnesium (Mg) and Iron (Fe). Test results show that water demand and setting times were not significantly changed by use of the FNS as cement replacement up to 50%. Le-Chatelier soundness test, autoclave expansion test and accelerated curing at 80 °C for 120 days showed no increase of expansion by up to 65% FNS despite its high magnesium content. This is because the Mg was found to be in the form of stable forsterite ferroan that did not take part in the hydration and expansive Mg(OH)2 (Brucite) was not found in the scanning electron microscope (SEM) images of the microstructure and powder X-ray diffraction (XRD). The 28-day strength activity index of the FNS was 84%. The 90-day mortar compressive strengths were 93% and 68% of the control specimen for 20% and 50% FNS respectively. Thus the soundness and strength development of the ground FNS were found comparable to those of other commonly used supplementary cementitious materials such as class F fly ash.